Indigofera zollingeriana as an Alternative Feed and Immunostimulant For Snakehead Fish Infected with Aeromonas hydrophila - Siti Lestari; Rizki Eka Puteri; Rani Ria Rizki; Guttifera; Donny Prariska; Raudhatus Sa'adah; Febby Hadi Setyawan; Ramanda Ahmad Rizal Rifa'i (Grouper, 2026)
The demand for snakehead fish in South Sumatra continues to increase, encouraging farmers to develop intensive cultivation. However, the main challenges of high feed costs and disease attacks need to be addressed to maintain optimal productivity. One alternative being studied is the use of Indigofera zollingeriana as a source of protein and immunostimulant in feed. This study aims to evaluate the effect of substituting fish meal with Indigofera flour on the immune response of snakehead fish (Channa striata) infected with Aeromonas hydrophila bacteria. The study used a Completely Randomized Design with four treatments of fish meal substitution with Indigofera zollingeriana flour, namely 0%, 15%, 30%, and 45%. The parameters observed included phytochemical tests, growth, blood profile, and water quality. The results of the phytochemical test showed the presence of flavonoids, alkaloids, tannins, and saponins. In the blood profile, the 45% treatment produced the highest erythrocyte value (4.54 × 10⁴ cells) and hematocrit of 38%. The best growth was shown in the 30% treatment with an SGR value of 2.56±0.23d and an FCR of 1.61±0.11a, while the highest survival rate (84.44%) was obtained in the 45% treatment. These findings indicate that Indigofera has the potential as a functional feed to improve the immunity and productivity of snakehead fish.